Bonum Coniugum Dalam Perkawinan - Joko, Antonius Padua Dwi (Lux et Sal, 2021)
The Catholic Church sees marriage as a living fellowship and an intimate love between a husband and a wife which is held by God and confirmed through His laws. As a consequence, a marriage institution is always a realization of God’s will that is concretely arranged by the ecclesiastical law. This point is confirmed by the Vatican Council II in Gaudium et Spes Constitution art. 48. From this point, the Code of Canon Law 1983, Cann. 1055 defines marriage as an agreement (feodus, consensus, covenant) between a man and a woman in order to establish a partnership of their whole life (totius vitae consortium). This view is different from the view of the Code of Canon Law 1917, Cann. 1012 which defines marriage as a contractus (a contract). Keeping in mind that marriage is a consensus, bonum coniugum (the good of the spouses) occupies an important, special, and equal place with the child’s birth and education. Husband or wife is a certain bonum and value which is cannot be used only as an object or instrument. In conclusion, the Vatican Council II and the Code of Canon Law 1983 immensely highlighted the personalistic and relational aspects of a marriage institution.